Signature of a partnership agreement between ISPD and RDPLF for French translation of ISPD guidelines. - Max Dratwa; Christian Verger (RDPLF, 2021)
We are pleased to announce with this new issue of the Bulletin de la Dialysis à Domicile (BDD), the bilingual journal of the RDPLF, the recent signing of a partnership agreement between the International Society of Peritoneal Dialysis (ISPD) and the RDPLF. The RDPLF now officially ensures the French translation of international open access recommendations published by the ISPD. The goal is to allow better distribution to French-speaking professionals who have difficulty accessing English-language medical literature.   In addition a webinar in French will be organized on an annual basis, in collaboration with the ISPD which will ensure logistics management. The dates will be communicated later. We warmly thank Professor Xueqing Yu, President of ISPD, and the members of the ISPD Board, for this agreement which will promote communication between health professionals who speak different languages. Max Dratwa, Christian Verger and the editorial committee.   Contents of this issue: - Assessment of Patient Experience of Care in Home Dialysis around the World: Enhancing the Patient's Voice in Home Dialysis Care and Research - Narrative interviews to assess quality of life in Peritoneal Dialysis -Chylous peritonitis in peritoneal dialysis - Peritoneal dialysis in indigenous Australians - French translation of ISPD Recommendations for the evaluation of peritoneal membrane dysfunction in adults: classification, measurement, interpretation and rationale for intervention - Home dialysis and Covid-19 in French speaking countries (RDPLF data-base) - Literature review (in French only) by the Young Nephrologists Club